Column-wall failure mode of steel moment connection with inner diaphragm and catenary mechanism. (15th January 2017) - Li, Ling; Wang, Wei; Chen, Yiyi; Teh, Lip H.
Highlights: A typical WUF-WW connection was tested and simulated in a column removal scenario. Column-wall failure mode was identified and compared with beam-end failure modes. This failure started with separation between bottom inner diaphragm and inside wall. Damage evolution of column-wall failure was independent of connection method for web. Connection undergoing column-wall failure effectively developed catenary mechanism. Abstract: Following the loss of an inner column, a moment resisting frame initially carries the upper load by the flexural mechanism with potential contribution from the catenary mechanism as the beams connected to the failed column deflect. The effective utilization of the catenary mechanism depends on the behaviour of the beam-to-column connections in the affected span. Previous studies have demonstrated that the types and details of the moment connections determine their behaviour, especially the failure mode, in the column removal scenario. Two typical failure modes, the beam-end continuous failure and the beam-end interrupted failure, have been studied in the literature. A third failure mode, identified as the column-wall failure, is investigated in this paper through a full-scale laboratory test and finite element (FE) simulations of an I beam-square hollow section column connection with inner diaphragms inside the column. The present experimental observation and FE analysis indicate that a column-wall failure starts with the separation between the bottom inner diaphragm and the column's inside wall, before fracture takes place in the column wall near the two ends of beam's bottom flange. The crack extends inwards along the bottom flange and finally upwards, at which point the flexural mechanism is fully replaced by the catenary mechanism. The column-wall failure mode is more desirable than the beam-end (or beam-section) continuous failure mode under the column removal scenario due to the former's ability to develop an effective catenary mechanism to bridge over the member failure of the column itself. In fact, the column-wall failure mode appeared to develop a more effective catenary mechanism than even the beam-end interrupted failure mode, although further research is required to ascertain the relative merits between the two modes and associated connection methods.